2015
DOI: 10.1063/1.4936921
|View full text |Cite
|
Sign up to set email alerts
|

Brush in the bath of active particles: Anomalous stretching of chains and distribution of particles

Abstract: The interaction between polymer brush and colloidal particles has been intensively studied in the last two decades. Here we consider a flat chain-grafted substrate immersed in a bath of active particles. Simulations show that an increase in the self-propelling force causes an increase in the number of particles that penetrate into the brush. Anomalously, the particle density inside the main body of the brush eventually becomes higher than that outside the brush at very large selfpropelling force. The grafted c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…Figure 3(b) shows that the horizontal inhomogeneity of particle distribution initially grows rapidly with propelling force and then gradually approaches a plateau. In contrast, the Gini coefficient of the horizontal distribution of ABPs in the 3D brush system 31 is small and almost independent of the propelling force, suggesting homogeneous horizontal distribution of ABPs (Fig. S1 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Figure 3(b) shows that the horizontal inhomogeneity of particle distribution initially grows rapidly with propelling force and then gradually approaches a plateau. In contrast, the Gini coefficient of the horizontal distribution of ABPs in the 3D brush system 31 is small and almost independent of the propelling force, suggesting homogeneous horizontal distribution of ABPs (Fig. S1 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 97%
“…As expected, with the increase of propelling force, more and more ABPs accumulate in the brush region, the same as our observation in the 3D system. 24 On the one hand, excluded-volume interactions between particles and chains tend to keep the particles outside the brush region. On the other hand, the grafted chains lower the mobility of trapped ABPs, and hence cause the accumulation of particles in the brush region (enhanced self-trapping mechanism).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an area of research that has received considerable interest and a number of analytical, numerical, and experimental results have been published on the subject [12,[66][67][68][69][70][71][72][73][74][75]. In fact, it has been shown that active fluids not only can generate a pressure on a boundary, but they can also induce exotic (depletion-like) effective forces between passive particles (tracers) with range and strength controlled by l p , that can be orders of magnitude larger than what expected for passive systems [73,[76][77][78][79][80][81][82][83][84]. These results suggest ways of designing microstructures to perform specific tasks when immersed in an active suspension.…”
Section: Active Colloidsmentioning
confidence: 99%
“…As a special case, polymer chains act as a deformable and movable boundary. The cooperation between the passive thermal motion of chain beads and the active non-thermal motion of particles leads to anomalous static and collective dynamic behaviors of the chains/active particles assembly [19][20][21][22][23].…”
mentioning
confidence: 99%